2001
DOI: 10.1086/321321
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraguild Predation and Stage Structure on Simple Communities along a Productivity Gradient

Abstract: Impact of intraguild predation and stage structure on simple communities along a productivity gradient Mylius, S.D.; Klumpers, K.; de Roos, A.M.; Persson, L. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
185
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(201 citation statements)
references
References 43 publications
10
185
5
Order By: Relevance
“…The HNF formed an intermediate prey in the heterotrophic food chain (bacteria/picophytoplankton-HNF-ciliates) and furthermore competed with O. tuberculata for bacteria and picophytoplankton. The reduction of B. saltans is consistent with the expectation that an omnivorous top consumer (i.e., here the ciliate) reduces its intermediate prey (e.g., Diehl and Feissel 2000;Mylius et al 2001) by feeding simultaneously on the intermediate prey and on the common basal resource ("strategy of eating your competitor"; Thingstad et al 1996). It is also consistent with the results of Rothhaupt (1996b) who showed that O. tuberculata eventually outcompetes B. saltans once the bacterial prey has been grazed down to a density that limits the growth of the HNF.…”
Section: Plankton Community Composition/invasion Dynamicssupporting
confidence: 84%
“…The HNF formed an intermediate prey in the heterotrophic food chain (bacteria/picophytoplankton-HNF-ciliates) and furthermore competed with O. tuberculata for bacteria and picophytoplankton. The reduction of B. saltans is consistent with the expectation that an omnivorous top consumer (i.e., here the ciliate) reduces its intermediate prey (e.g., Diehl and Feissel 2000;Mylius et al 2001) by feeding simultaneously on the intermediate prey and on the common basal resource ("strategy of eating your competitor"; Thingstad et al 1996). It is also consistent with the results of Rothhaupt (1996b) who showed that O. tuberculata eventually outcompetes B. saltans once the bacterial prey has been grazed down to a density that limits the growth of the HNF.…”
Section: Plankton Community Composition/invasion Dynamicssupporting
confidence: 84%
“…The above equation is our second assumption and has been recognized as a general feature promoting the existence of intra-guild predation as a feasible trophic mode [14,36,37]. Notice how this assumption can be linked to the concept of 'trophic upgrading' [38], namely the feasibility of omnivory as a trophic mode is assured provided that the net trophic efficiency to the omnivore via intraguild predation exceeds that of feeding on the resource directly.…”
Section: Stabilitymentioning
confidence: 99%
“…Models suggest that IG predation should be rare (Holt and Polis 1997;Mylius et al 2001), yet it is frequently documented in natural systems (Palomares and Caro 1999;Donadio and Buskirk 2006). However, these models fail to account for individual antipredator behavior that could lead to Communicated by Janne Sundell.…”
Section: Introductionmentioning
confidence: 99%